A user‐centered, learning asthma smartphone application for patients and providers - Mark Gaynor; David Schneider; Margo Seltzer; Erica Crannage; Mary Lee Barron; Jason Waterman; Andrew Oberle (Wiley, 2020)
Abstract Problem Smartphone applications are an increasingly useful part of patients' self‐management of chronic health conditions. Asthma is a common chronic health condition for which good self‐management by patients is very helpful in maintaining stability. User‐centered design and intelligent systems that learn are steps forward in building applications that are more effective in providing quality care that is scalable and tailored to each patient. Methods A literature and application store search to review historic and current asthma smart phone applications. User‐centered design is a methodology that involves all stakeholders of a proposed system from the beginning of the design phase to the end of installation. One aspect of this user‐centered approach involved conducting focus groups with patients and health care providers to determine what features they desire for use in applications and create a model to build smart infrastructure for a learning health care system. A simple prototype for an asthma smartphone application is designed and built with basic functionality. Outcomes Only one publication in the literature review of asthma smartphone applications describes both user‐centered design and intelligent learning systems. The authors have presented a set of user‐desired attributes for a smart health care application and a possible data flow diagram of information for a learning system. A prototype simple user‐centered designed asthma smartphone application that better assists patients in their care illustrates the value of the proposed architecture. Discussion Our user‐centered approach helped design and implement a learning prototype smart phone application to help patients better manage their asthma and provide information to clinical care providers. While popular in other industries, user‐centered design has had slow adoption in the health care area. However, the popularity of this approach is increasing and will hopefully result in mobile application that better meets the needs of both patients and their care providers.